Quality Evaluation in Hospital Operations Management Using Multi-Criteria Decision-Making with Plithogenic Approach to Address Uncertainty and Enhance Decision-Making Processes - Meng Zhang; Yafang Li (Neutrosophic Sets and Systems)
Coordination of medical facilities' operations depends on operations management. Hospitals must function effectively to meet the medical demands of their patients, who get critical and emergency treatment. The decision support system for Quality Evaluation in Hospital Operations Management is created in this study. Plithogenic sets and multicriteria decision-making (MCDM) form the foundation of this decision assistance system. The study presents a novel approach to evaluating and rating Hospital Operations Management. Alternatives are ranked using the plithogenic reference-based normalization alternative ranking (RBNAR) technique. Thus, the algorithm for plithogenic-RBNAR is constructed and presented. An analysis of Hospital Operations Management is conducted using the new hybrid decision support model. The plithogenic-RBNAR hybrid method's applicability is supported by the research findings. The case study and sensitivity analysis results support the plithogenic-RBNAR hybrid model's robustness and applicability.